Eksplorasi Faktor-Faktor Yang Mendorong Dan Menghambat Disiplin Belajar Siswa Di STTD Al Birru Majenang - Damayanti, Alif Fia; Ardani, Anisa Rahayu; Imtiyas, Mauhibah Nur; Mustofa, Amrin (Universitas Pakuan, 2026)
Exploration of Factors That Encourage and Hinder Student Learning Discipline at STTD Al Birru Majenang Student learning discipline serves as the primary foundation for educational success at STTD Al Birru Majenang, an institution for training elementary-level Islamic religious teachers. This research explores the factors promoting and inhibiting student learning discipline in depth. Employing a qualitative approach with a case study method, data were collected through in-depth interviews with 5 students, classroom observations, and school document analysis over two months. Promoting factors include the teacher's role as an Islamic role model, a conducive learning environment integrating moral values, and parental support through family education. Conversely, inhibiting factors encompass inadequate learning facilities, the influence of gadgets and social media, and students' household chores burden. Findings indicate that strengthening a holistic Islamic-based approach effectively enhances discipline. This study recommends that STTD Al Birru management optimize character-building strategies to achieve quality educational goals.